Menguji Autentisitas Akademik Orientalis dalam Studi Islam - Thoha Hamim (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article seeks to objectify our understanding in the term of Orientalist, in addition we test the authenticity of the studies that have been developed by the Orientalists. Critics of Orientalism is actually done by Western scholars indicate the passage of the principle of freedom of thought which underlies the research activities of academics in the West. With such academic freedom, the scholars had to deconstruct the Orientalist negative thoughts about Islam, though the thought is already crystallized into a mainstream standard. Institutional development of Islamic studies in the West in recent decades has experienced a change in orientation, to adjust to his position as a medium to establish understanding between program participants across cultural boundaries, traditions, and religion. Nevertheless, suspicion of the activities of Islamic studies in the West is carried out by Muslim students still exists as a precautionary catch against the possibility of erosion of confidence.